Construction process of a novel multi-degree of freedom parallel passive compliant constant-force mechanism. (December 2022) - Li, Baokun; Han, Yingge; Zhang, Mingkun; Li, Yanbiao; Sun, Lunye
Based on the configuration of the Stewart parallel mechanism (SPM), after analyzing the kinetostatic characteristic of a planar four-bar linkage with attached springs which works around the kinematic limb-singularity, a process of constructing a novel multi-degree of freedom (DOF) parallel passive compliant constant-force mechanism (CCFM) is presented. The kinematic limb-singularity of a rigid four-bar linkage with attached springs is obtained and then is applied to construct a constant-force compliant mechanism (CM) based on the pseudo-rigid-body-model by designing appropriate structure parameters to obtain appropriate equivalent spring stiffness of flexures. The CCFM is further used as the branches of the SPM and then a passive multi-DOF parallel mechanism (PM) is constructed. Here the method of replacing the original rigid branch of the PM with the CCFM is called the "Expanded Rigid-body Replacement Synthesis" (ERBRS). The multi-DOF parallel passive CCFM can generate a constant-force zone when makes a small pose transformation around a certain position, where each compliant branch is located at the constant-force zone. The proposed CCFM can be applied in practice such as the polishing machine which needs the constant contact-force between the polishing head and the workpiece. The proposed method of constructing a CCFM with one- or multi-degree of freedom mechanism has some important reference value on designing other types of CCFMs.